Investigating Pre-Service English Teachers’ Perception on the Use of Multimedia in EFL Teaching and Learning Process: Pedagogical Implication - Didih Faridah; Leni Irianti; Reska Laila Fachriyani (Yayasan Karinosseff Muda Indonesia, 2020)
This paper reports on investigating pre-service English teachers’ perceptions on the use of multimedia in EFL teaching and learning process: pedagogically implication. This research aimed to investigate the pre-service English teachers’ perception toward the use of multimedia in EFL teaching and learning process and to observe kind of multimedia are used by the pre-service English teachers’ in EFL teaching and learning process. The participant of this research was the 63 senior students of English Department Galuh University. The questionnaire and interview were the instruments used in this research to collect the data. Survey monkey application was used in analyzing the questionnaire by displaying it into the figure and data interpretation based on the answer from a close-ended questionnaire, while the data from telephone interviews were analyzed by displaying data interpretation from the interviewees. After having the findings, the research showed that the students had a positive attitude towards multimedia. Most of the participants agreed that they like multimedia because it helped them in the teaching and learning process. In this era, we can easily found multimedia. PowerPoint, YouTube Videos, Podcast, Canva, PowToon, Picture, CALL, MALL, Digital Comic, Song, PowToon, and Movie are some the kinds of multimedia that can be used by pre-service English teachers' as the solution to make the learning process more interesting and enhance the students' language pedagogy. This research concludes that using multimedia in the teaching and learning process was important to improve their achievements, understanding, performances, and to achieve objectives of language pedagogy.